ENHANCING PURCHASE DECISIONS IN UD. MANDIRI TOPORE BUILDING STORE, MAMUJU DISTRICT: THE IMPACT OF PRODUCT DIVERSITY AND BRAND TRUST - Dandi Rivaldi; Iwan Adinugroho; Suharlina Suharlina (SEAN Institute, 2023)
This study examines the influence of product diversity and brand trust on purchasing decisions at UD. Mandiri Topore Building Store in Mamuju Regency. The analysis was conducted using multiple linear regression and statistical tests. The results indicate that both variables,